Recent philanthropy strides: Lessons for Islamic philanthropy - S. Saidu, Oluwaseun; Oguntola, Mulkat A. (Online Journal of Research in Islamic Studies, 2015)
The â€œmainstreamâ€ philanthropy literature is awash with varying strands of â€œknowledgeâ€ ranging from giving strategies or giving policies as well as themes that explain giving behaviour all in a bid to increase giving behaviour consistently. The paper seeks to expound if there is any lesson to be learnt from the gargantuan amount of scholarly philanthropy enterprise when viewed from the Islamic prism. Particularly, the authors aim to spell out if any, implications for Islamic philanthropy from these philanthropic strides.